2020
DOI: 10.1177/0164027520948192
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging Attitudes on the Quality of Life of Older Adults in China

Abstract: We use data from the 2014 China Longitudinal Aging Social Survey to examine the effect of attitudes toward aging on quality of life among older adults in China. We find that older people who experience psychosocial loss may be less satisfied with their life, and have more feelings of depression and loneliness. Compared to older women, older men have lower life satisfaction, and more depression and loneliness, though psychosocial loss has less of an effect on them. Older women who experience psychosocial loss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Our results verifies the relationship between aging attitudes and loneliness among the Chinese elderly, which has been found in prior research ( Chen et al, 2021 ). On the one hand, older adults with a positive attitude toward aging may experience less loneliness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results verifies the relationship between aging attitudes and loneliness among the Chinese elderly, which has been found in prior research ( Chen et al, 2021 ). On the one hand, older adults with a positive attitude toward aging may experience less loneliness.…”
Section: Discussionsupporting
confidence: 91%
“…Empirical studies examining the association between attitudes toward aging and loneliness among the Chinese elderly are scarce. According to Chen et al (2021) , both positive and negative attitudes toward aging significantly impact loneliness among the Chinese elderly, but there are considerable disparities between groups. Furthermore, Zeng et al (2022) proposed that attitudes toward aging play an essential role in alleviating the loneliness of the elderly.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Influenced by such factors as increasing life expectancy and decreasing fertility rate, the growth rate and scale of China’s population aged 60 and above exceeds that of most developed countries [ 1 ]. Census data released by China’s National Bureau of Statistics shows that from the fifth census in 2000 to the seventh census in 2020, China’s population aged 60 and above increased from 126 to 264 million, accounting for 18.7% of the total, up from 10.2%.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2020, China has reported 4.57 million new cancer cases and 3.00 million deaths, respectively accounting for 24% of newly diagnosed cases and 30% of cancer-related deaths worldwide [ 3 ]. Furthermore, China has the largest elderly population and fastest aging speed in the world [ 4 ]. Prior research has shown that cancer morbidity and mortality rates increase with age, and at present, older adults constitute more than 60% of cancer patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%